2018
DOI: 10.3389/fendo.2018.00326
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Level and Activities of Daily Living in Octogenarians: Cross-Sectional Study

Abstract: IntroductionDespite the growing number of octogenarians, little is known about their vitamin D status and activities of daily living (ADL) relations.ObjectiveThe aim of this study was to investigate peculiarities of vitamin D and ADL and to assess their relations in octogenarians.MethodsA cross-sectional study was performed at the National Osteoporosis Centre located in Vilnius, Lithuania. Community-dwelling ambulatory persons aged ≥80 years were included. Current users of vitamin D supplements were excluded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Previous prospective studies indicated that higher consumption of dairy products is associated with a lower risk of functional disability [13]. Nutrients, such as vitamin D [14] and dietary fiber [15], are also reported to be related to ADL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous prospective studies indicated that higher consumption of dairy products is associated with a lower risk of functional disability [13]. Nutrients, such as vitamin D [14] and dietary fiber [15], are also reported to be related to ADL.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically on BADL, it is already established that deficient serum 25(OH)D increases the risk of incidence of disability [ 25 , 35 , 36 ]. Nevertheless, even with evidence of a cross-sectional association between low serum 25(OH)D concentrations and low IADL scores [ 17 , 18 ], longitudinal association between serum 25(OH)D concentrations and incident IADL disability remains rarely explored and with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional evidence has already shown that older adults with deficient serum 25(OH)D have a higher IADL impairment score compared to individuals with serum sufficiency [ 17 , 18 ]. In parallel, a longitudinal study showed that older women with deficient serum 25(OH)D at baseline had a greater functional decline in IADL at 2 years of follow-up [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These eight scoring items followed previous studies. Previous researched included these items included in the scale assessed were as previous research ( Alekna et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%